Step * 2 1 1 1 1 1 of Lemma extended-face-map

.....assertion..... 
1. Cname List
2. x1 Cname
3. (x1 ∈ I)
4. x2 Cname
5. (x2 ∈ I)
6. : ℕ2
7. y1 Cname
8. y2 Cname
9. ¬(y2 ∈ I-[x1; x2])
10. ¬(y1 ∈ I)
⊢ [y1 I-[x1; x2]] [y1 I]-[x1; x2] ∈ (Cname List)
BY
Assert ⌜¬(y1 ∈ [x1; x2])⌝⋅ }

1
.....assertion..... 
1. Cname List
2. x1 Cname
3. (x1 ∈ I)
4. x2 Cname
5. (x2 ∈ I)
6. : ℕ2
7. y1 Cname
8. y2 Cname
9. ¬(y2 ∈ I-[x1; x2])
10. ¬(y1 ∈ I)
⊢ ¬(y1 ∈ [x1; x2])

2
1. Cname List
2. x1 Cname
3. (x1 ∈ I)
4. x2 Cname
5. (x2 ∈ I)
6. : ℕ2
7. y1 Cname
8. y2 Cname
9. ¬(y2 ∈ I-[x1; x2])
10. ¬(y1 ∈ I)
11. ¬(y1 ∈ [x1; x2])
⊢ [y1 I-[x1; x2]] [y1 I]-[x1; x2] ∈ (Cname List)


Latex:


Latex:
.....assertion..... 
1.  I  :  Cname  List
2.  x1  :  Cname
3.  (x1  \mmember{}  I)
4.  x2  :  Cname
5.  (x2  \mmember{}  I)
6.  i  :  \mBbbN{}2
7.  y1  :  Cname
8.  y2  :  Cname
9.  \mneg{}(y2  \mmember{}  I-[x1;  x2])
10.  \mneg{}(y1  \mmember{}  I)
\mvdash{}  [y1  /  I-[x1;  x2]]  =  [y1  /  I]-[x1;  x2]


By


Latex:
Assert  \mkleeneopen{}\mneg{}(y1  \mmember{}  [x1;  x2])\mkleeneclose{}\mcdot{}




Home Index